Association of HDL Cholesterol with In-Hospital Outcome of Patients with Acute Coronary Syndrome (Bangladesh Heart Journal, 2018)
Background:Acute coronary syndrome is a cardiac emergency. It is increasing dramatically and becoming a major burden in our health care system. Relation between serum lipid profile and acute coronary syndrome is well established. Our study tried to reveal association of high density lipoprotein cholesterol (HDL-C) with in-hospital outcome of patients with acute coronary syndrome.Methods: The study was a cross sectional comparative study. Clinical & biochemical evaluation was done in hospital settings. A total number of 271 patients were included in the study and divided into two groups. Patients with low HDL-C level were in group I and patients with normal HDL-C were in group II.Results: Group I populations had more complications & more in- hospital stay than group II (74.3% vs 28.9%, P